PEMBERDAYAAN MASYARAKAT UNTUK MEMBERIKAN PILIHAN PELUANG USAHA MANDIRI BAGI KELOMPOK KOMISI KAUM WANITA GSJA MARANATHA - MALANG - Tri Istining Wardani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The aim of this community service is to provide material enrichment on entrepreneurship in the concept of empowering the hidden potential and creativity of the core members of a household, especially for the Women's Commission group in GSJA Maranatha Malang. The activity this time the Women's group was chosen as the target audience with the consideration of women has the instinct to be responsible for family welfare. Through entrepreneurship skills enrichment activities are expected to be useful to trigger the motivation and creativity of women so they can have skills that can be used independently to help the economy and family welfare. This community empowerment activity is divided into two modules, the first by providing a theoretical briefing on the objectives, benefits and tips of running entrepreneurial activities, as well as the importance of running an independent business for a woman to improve family welfare. While the second provides enrichment of the basic single and double crochet knitting skills through the Granny-Pattern technique training, which is processing yarn by forming loops with the help of a hook bar so as to form an object with new use values. Training is carried out with direct way to provide opportunities for the target audience to practice accompanied by a facilitator and produce a product that has a sale value, and still has a potential market in the community, such as pillowcases, bed sheets, bed-covers and tablecloth. Based on the results of the training evaluation, it can be concluded that the training runs smoothly and effectively because the target audience can absorb the knowledge delivered and be able to produce the finished product according to what was targeted from the start.